Analysis of Metacognition Ability and Critical Thinking Skills of Students in Integrated Islamic Education Institutions - sukarno -; AA Musyafa (INNOVATIO: Journal for Religious Innovation Studies, 2021)
Abstract: Metacognition and critical thinking skills are essential elements in creating good quality and competitive humans in the future. Therefore, this study aims to describe students' metacognitive abilities and critical thinking skills in Integrated Islamic Junior High School in Jambi. The writer uses a quantitative approach in this study and survey techniques to collect the data. There are 200 students from various Integrated Islamic Junior High Schools in Jambi involved in this study. After validating the data through validated instruments, the research reveals that: (1) The highest metacognitive ability of students at the Integrated Islamic Junior High School is in Procedural Knowledge (PK), which is an average value of 7.4 in the "good" category. Cognition Management (P) and Management of Information Management (IMS), with an average score of 6.6 and 6.5, respectively, are in a suitable category. The lowest metacognitive ability is the ability of self-evaluation ability (3,1) in the "low" category, while other abilities are in the "medium" category, (2) the critical thinking ability of students at Integrated Islamic Junior High School in Jambi is relatively good. As many as three of the five measured aspects are in the "good" category, and the rest (two aspects) are in the "medium" category. Thus, no aspect is measured to have the ability with the "low" category. In general, it shows that students' critical thinking on average at the Integrated Islamic Junior High School in Jambi have good critical thinking skills. Abstrak: Kemampuan metakognisi dan keterampilan berpikir kritis merupakan dua elemen panting dalam menciptakan manusia yang bermutu dan berjiwa kompetitif dimasa depan. Oleh karena itu, penelitian ini bertujuan untuk mendeskripsikan kemampuan metakognisi dan keterampilan berpikir kritis siswa SMP Islam Terpadu di Jambi. Penelitian ini meggunakan pendekatan kuantitatif dengan teknik pengambilan data melalui teknik survey. Penelitian ini melibat 200 peserta didik dari berbagai sekolah SMP Islam Terpadu di Jambi. Berdasarkan data yang telah diambil dapat disimpulkan bahwa: (1) Kemampuan metakognisi tertinggi siswa pada sekolah SMP Islam Terpadu adalah pada Pengetahuan Prosedural (PK) yaitu nilai rata-rata 7,4 dengan kategori “baik”. Selanjutnya disusul dengan kemampuan Pengaturan Kognisi (P) dan Manajemen pengelolaan informasi (IMS), yaitu masing-masing memiliki skor rata-rata 6,6 dan 6,5 dengan kategori baik. Adapun kemampuan metakognisi terendah adalah kemampuan Kemampuan evaluasi diri (3,1) dengan kategori “rendah”, sedangkan kemampuan lainnya berkategori “sedang”, (2) kemampuan berpikir kritis siswa pada SMP Islam Terpadu di Jambi, relative sudah baik. Sebanyak tiga dari lima akpek yang diukur berada pada kategori “baik” dan sisanya (dua aspek) berada pada kategori “sedang”. Dengan demikian tidak ada aspek yang diukur memiliki kemampuan dengan kategori “rendah”. Hal itu menunjukkan bahwa secara umum atau rata-rata siswa di SMP Islam Terpadu di Jambi memiliki kemampuan berpikir kritis yang baik. Kemampuan tersebut dapat dilihat dari aspek: kemampuan dalam memberikan penjelasan sederhana, Kata-kata kunci: Kemampuan metakognisi, keterampilan berpikir kritis, SMP Islam Terpadu